Using Design of Location-Based Augmented Reality Experiences to Engage Art-Oriented Girls in Technology and Science - Davis, Cathlyn Merritt; Kamarainen, Amy; Storksdieck, Martin; Gagnon, David; Kermish-Allen, Ruth; Riedinger, Kelly (Frontiers in Education, 2021)
Taking part in creating location-based augmented reality (LBAR) experiences that focus on communication, art and design could serve as an entry point for art-oriented girls and young women towards career pathways in computer science and information communication technology. This conceptual paper presents our theory-based approach and subsequent application, as well as lessons learned informed by team discussions and reflections. We built an LBAR program entitled AR Girls on four foundational principles: stealth science (embedding science in familiar appealing experiences), place-based education (situating learning in one’s own community), non-hierarchical design (collaborations where both adults and youth generate content), and learning through design (engaging in design, not just play). To translate these principles into practice, we centered the program around the theme of art by forming partnerships with small community art organizations and positioning LBAR as an art-based communication medium. We found that LBAR lends itself to an interdisciplinary approach that blends technology, art, science and communication. We believe our approach helped girls make connections to their existing interests and build soft skills such as leadership and interpersonal communication as they designed local environmentally-focused LBAR walking tours. Our “use-modify-create” approach provided first-hand experiences with the AR software early on, and thus supported the girls and their art educators in designing and showcasing their walking tours. Unfortunately, the four foundational principles introduced considerable complexity to AR Girls, which impacted recruitment and retention, and at times overwhelmed the art educators who co-led the program. To position AR Girls for long-term success, we simplified the program approach and implementation, including switching to a more user-friendly AR software; reducing logistical challenges of location-based design and play; narrowing the topic addressed by the girls’ design; and making the involvement of community partners optional. Overall, our initial work was instrumental in understanding how to translate theoretical considerations for learning in out-of-school settings into an LBAR program aimed at achieving multiple complementary outcomes for participating girls. Ultimately, we achieved better scalability by simplifying AR Girls both conceptually and practically. The lessons learned from AR Girls can inform others using LBAR for education and youth development programming.